Aesthetics of Surrealist Elements in "Nadia" by Andre Burton and "Three Drops of Blood" by Sadegh Hedayat - Amene Erfani Fard; Kazem Dezfoulian (Matn/Pizhūhī-i Adabī, 2024)
Art and aesthetics are broad components through which the world is interpreted, affecting imagination, creation and expression in a perceptual process. Aesthetic experience and knowledge challenge new methods and perspectives of the mind. "Nadia" by Andre Burton and "Three Drops of Blood" by Sadegh Hedayat serve as clear examples of objective and mental beauty elements that reveal the hidden reality of the deep mental state of man in his subconscious mind. They possess an ontological reality of which our consciousness has only grasped a small part. The purpose of analyzing the aesthetic elements of these works, which represent the needs of different areas of human life through intuition, reflection and attention to the transcendental world, is to create an interactive connection between human feelings, thoughts, wisdom and imagination. The goal is to understand how these works are written and why they hold value. In this research, using a descriptive and analytical method and the approach of comparative literature, we rely on the American critical school for qualitative analysis of the surrealistic aesthetic aspects of the works. We have concluded that the beauty of language and imagination in the superstructure part, and the beauty of the content in the deep construction part using the techniques of surrealism, are the constructive foundations of the beauty of these works that lead to the creation of spaces that is a rebellion to free the mind from limitations.IntroductionPost-Modernist art evaluates history solely through an aesthetic lens. This aesthetic approach to the world not only captures human attention and cognitive activity, but also delves into understanding the logic of human emotions and how they are conveyed, expanding mental spaces and consciousness while highlighting the importance of imagination. Engaging with the arts opens one's mind to new interpretations and possibilities. Surrealism, as a school of thought, has transitioned from a mere technique to a profound theory and aesthetic, ushering its audience into a new era of epistemology. In this realm, artists strive to liberate themselves from the constraints of reason and sensory perception in order to externalize their innermost selves through their artwork.Sadegh Hedayat's "Three Drops of Blood," with its dreamlike style and imaginative depiction of conflicting and complex elements, serves as a testament to the author's unique perspective on the deepest layers of Iranian human existence, offering a historical and social narrative that resonates with society and the world at large. Similarly, André Burton's groundbreaking surrealist novel "Nadia" blends reality with imagination, presenting profound mental imagery that transcends the boundaries between dream and reality, ultimately culminating in a new, absolute reality. Both works, through their narrative and descriptive exploration of objective and subjective spaces, aim to address the diverse facets of human life by tapping into intuition, reflection, and an understanding of the metaphysical world, fostering an "interactive" connection between human emotion, thought, reason, and imagination.This study aims to uncover the fundamental similarities between these two remarkable works within the literary and aesthetic context of surrealism, addressing the following questions: To what extent can the aesthetic approach of Surrealism discern its core elements, such as the blurring of reality, the dissolution of boundaries, the abandonment of dogma and certainty, and a deeper understanding of the profound human issues scattered throughout the universe? How can we gain a partial understanding of unknown worlds, both in the East and the West, by exploring surrealist works and grasping their essence and significance?Literature ReviewSince the present study compares and examines surrealist aesthetic aspects in Iranian and French literature and its reflection in two famous authors, Sadegh Hedayat, and André Breton, it is necessary to introduce a background of the first comprehensive and relevant studies on these works. Works such as Critique and Interpretation of Sadegh Hedayat's Works by Mohammad Reza Ghorbani, Psychological Analyses in Art and Literature by Mohammad Sanati, Analysis of "Three Drops of Blood" by Ali Taslimi (2009), "Failure to Speak: A Psychoanalytic Narrative of the Story of Three Drops of Blood" by Hussein Payandeh (1990), "A Study of Three Drops of Blood" based on Michel Foucault's theory of power by Abbas Khaefi (2012)."Nadia, A World of Wonder Beauty" interviewed: Abbas Pejman (2012) is also a work written about Nadia's book. The difference of the present study is in the design of the aesthetic and literary perspective of the Surrealist school to the following texts.MethodologyIn this study, with a comparative approach and according to the American school of criticism, we have explained and analyzed the aesthetic elements of surrealism in the book "Nadia" and "Three Drops of Blood". The aesthetic components of surrealism used in this research to analyze the content of the works include 1. Satire, which with its sudden and improvised words and images, disturbs the mind and humiliatees the absurdities of the world; 2. The Wonder and the Magic, which tries to understand the world of illusions and ghosts, the world of imagination and dream, and the unconscious world; 3. Automatic writing in which incoherent words and sentences depict the passion and internal energies of the text without the interference of the mind; 4. The dream, that reveals the distorted nature of reality and opens the gates of discovery and intuition in the text; 5. Madness, is the ultimate goal of dreaming to reach the source of true knowledge; 6. Finally, surrealist objects, disturb our conception of reality due to their associated quality and their strange presence and function.  ConclusionIn surrealist aesthetics, art can make any material acceptable to attitude and emotion and remind us that human history and story can never end. The aesthetic approach of Surrealism seeks to understand and identify the fundamental elements of reality, boundaries, events, and concepts to understand the hidden angles of deep human issues and to gain a relative understanding of unknown worlds in the field of human thought and its quality and nature. Therefore, Nadia's book is a new way of discovering intuition in the text and the universe and seeking to show the space and emotions embedded in the world of the text. However, "Three Drops of Blood" is based on historical, social and political backgrounds and seeks to show the more precise nature of the human psychic layers and the truth of human life, which depicts unknown attitudes and feelings and how they act coherently in reflecting on the discovery of secrets and stepping into the hidden wonders and layers of the human psyche in a single manifestation.The influence of space and the prelude that the narrator provides three drops of blood to make the story believable, with its broad implication and flexible expression, acts to instill a single concept, various signs that bear witness to the encounter with the deep layers of the collective unconscious of contemporary Iranian. In this work, instead of uniting with his world, the narrator is torn apart to portray the helplessness of man in his ruined and lonely life today, caught in its historical decay and corruption. In his images, certainty falters, boundaries are pushed aside, and common objects and concepts lose their dogma and find different concepts. In contrast to the world of Nadia, whose idea is unified and consistent in the narrator's psyche. Nadia, despite the degenerate and disheartening suffering, talks about deep human issues, but she links consciousness and perception in understanding this concept with elements such as confrontation, similarity, and repetition of the image to achieve beauty with pleasure. However, the existence of elements such as suffering, loneliness, and the misery of life amid all the sufferings of the soul in a maddening environment, while also touching contemporary man, has marked both works. Hence the work may be pitiful in its exterior, in its glory, and speak only of deep destruction and unbreakable fissures. But the language of the work is richer and more rebellious to achieve freedom of the mind from restrictive elements, whether literary boundaries or methods of writing and reading texts. So, the common aspect of the two works on the one hand is the human nature and the mental, intellectual, and spiritual foundations of human beings that are similar in every place, time, and place, and on the other hand, civilizational similarities between Iranian and European (French) thinking return which has a human basis.